Consenso à brasileira: Exame da justiça consensual criminal sob perspectiva antropológica - Almeida, Vera Ribeiro de (2014)
Este artigo analisa as práticas de atualização do consenso e da verdade processual por meio da observação da aplicação de um instituto próprio dos Juizados Especiais Criminais: a transação penal. Por meio de pesquisa qualitativa em JECrims estaduais da Baixada Fluminense (integrante de um estudo mais abrangente nesses órgãos), baseada na interpretação dos discursos dos operadores jurídicos desses órgãos, na descrição etnográfica e na observação participante de suas práticas e na comparação desse material com o discurso legal e doutrinário, reflete-se sobre as garantias processuais próprias do estado democrático de direito no sistema brasileiro. The article Brazilian Style Consensus: Examination of Consensual Criminal Justice from an AnthropoÂlogical Perspective analyses the practices of modifying consensus and truth by observing the application of an institute belonging to the Magistrates' Courts: the plea bargain. A qualitative study into the state Magistrates' Courts of the Baixada Fluminense region was conducted as part of a broader study at these courts, based on inÂterpretation of the arguments of the legal operators of the courts, and ethnographic description and participaÂtive observation of its practices. These findings were then compared to the legally indoctrinated discourse to lead to reflection on the procedural guarantees typical of the democratic state of law in the Brazilian system.Keywords: ‘transação penal', legal anthropology, consensus, legal truth, legal actors